1996
DOI: 10.1207/s15327663jcp0501_03
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Purchase Intentions for an Environmentally Sensitive Product

Abstract: Expressions of positive attitudes toward the environment are only weakly related to the consumption of alternatives to products that are environmentally unfriendly. Yet, socially concerned marketers and public policy makers still appeal to general environmental concern (GEC) when trying to demarket environmentally sensitive products or market more friendly alternatives. In this article, we propose that GEC has an indirect effect on purchase intentions for environmentally related products and the relation is me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
108
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(120 citation statements)
references
References 34 publications
9
108
1
2
Order By: Relevance
“…Thus, the ideal sample for this study consisted of adults (age 18 years or older). Furthermore, many researchers have suggested that people with less education find it hard to understand the topic under consideration compared to those with higher education [2,57,[105][106][107]. Therefore, quota sampling technique was used in this study to select respondents of or over 18 years of age and having a minimum education level of high school that resided in Thailand.…”
Section: Sample and Data Collectionmentioning
confidence: 99%
“…Thus, the ideal sample for this study consisted of adults (age 18 years or older). Furthermore, many researchers have suggested that people with less education find it hard to understand the topic under consideration compared to those with higher education [2,57,[105][106][107]. Therefore, quota sampling technique was used in this study to select respondents of or over 18 years of age and having a minimum education level of high school that resided in Thailand.…”
Section: Sample and Data Collectionmentioning
confidence: 99%
“…Even if consumers express environmental concerns (Alwitt and Pitts 1996), environmentally friendly features may remain peripheral if there is no personal threat (ThĂžgersen 2000), because they will not be integrated into the overall quality assessments in normal food product evaluations. Because of its associations with benefits such as taste, health, and concern for the environment (Hughner et al 2007), the presence of an organic label should activate corresponding cues and make these attribute more salient to judgments of overall product quality.…”
Section: Reinforcing the Salience Of Environment Friendliness For Promentioning
confidence: 99%
“…Alwitt and Pitts(1996) emphasized the importance of environmental-friendly consumer purchasing behavior as they clarified that environmental interest influence environment related product purchasing intentions.…”
Section: Artificial Leather Fashion Product Purchasing Intentionsmentioning
confidence: 99%